The use of individual protection equipment for nurses of a hospital - Mayara de Oliveira Fernandes; Kátia Nêyla de Freitas Macêdo-Costa; Grazielle Roberta Freitas da Silva; Patricia de Lemos Negreiros (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2008)
Introduction: The individual protection equipment(IPE) is of measures to minimize and even though to eliminate hazards to worker's health. Its use is essential in the environment of worker's nursing. Aims: To observe the use of the IPE for nurses in a hospital. Materials and Method: Observation research's quantitative through in julho/2007, on small hospital in the Ceará. It was carried through with 05 nurses, in which if it used an instrument of the type check-list. The data had been organized and analyzed in pictures and graphics and subdivided for procedures. Results: The following procedures had been observed: peripheral venous of long permanence, auscultation pulmonary, dressing, probe delay vesical, vaginal childbirth, orotraqueal aspiration, vaginal touch and vaccination. Lack of the protection equipment was identified; however it had the use on the part of the nurses. The closed shoes had been the equipment most used, followed the glove, the dressing gown and the mask. The cap and the eyeglasses had not appeared. Conclusions: Due to the hazards occupational exposition in the hospital attendance, them they need to be acquired knowledge beyond demanding of the institutions the acquisition and use of the IPE.